2014
DOI: 10.1073/pnas.1401782112
|View full text |Cite
|
Sign up to set email alerts
|

Carbon-bearing iron phases and the carbon isotope composition of the deep Earth

Abstract: The carbon budget and dynamics of the Earth’s interior, including the core, are currently very poorly understood. Diamond-bearing, mantle-derived rocks show a very well defined peak at δ13C ≈ −5 ± 3‰ with a very broad distribution to lower values (∼−40‰). The processes that have produced the wide δ13C distributions to the observed low δ13C values in the deep Earth have been extensively debated, but few viable models have been proposed. Here, we present a model for understanding carbon isotope distributions wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
22
2
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(28 citation statements)
references
References 62 publications
2
22
2
2
Order By: Relevance
“…In each step the metal equilibrates with the silicate magma ocean, and it remains chemically isolated once it segregates in the core. The fractionation of light element isotopes in this model can best be described by the Rayleigh distillation model (Wood et al, 2013;Horita and Polyakov, 2015) (Fig. 3).…”
Section: Resultsmentioning
confidence: 99%
“…In each step the metal equilibrates with the silicate magma ocean, and it remains chemically isolated once it segregates in the core. The fractionation of light element isotopes in this model can best be described by the Rayleigh distillation model (Wood et al, 2013;Horita and Polyakov, 2015) (Fig. 3).…”
Section: Resultsmentioning
confidence: 99%
“…For comparison the theoretical computation of fractionation between diamond and iron carbide is also shown (after Ref. [15]). The vertical line represent a possible temperature of crystallization of iron melt, which will correspond to a fractionation of 2.…”
Section: Carbon Isotope Fractionation At High-pressure and High-tempementioning
confidence: 99%
“…Thus far, the heterogeneities in carbon isotopic composition in the upper mantle have been explained mainly by recycling process. However, recent studies have suggested the possible presence of 12 C enriched carbon in the core by fractionation processes during early accretion and segregation of metallic core [14,15]. Studies on other planetary materials in the solar system, such as howardite-eucrite-diogenite (HED) meteorites, shergottite-nakhlite-chassignite (SNC) meteorites and chondrites suggest that there is a remarkable difference in isotopic composition between these bodies and bulk silicate Earth values, the later being heavier than the former in the order of about 10 to 15 [16][17][18].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, the Earth's core could contain significant C, resulting in a fractionated mantle (20). In any case, I think it is worth considering that at its beginning, the Earth was highly reducing and had significant 13 C-depleted carbon in its upper mantle.…”
mentioning
confidence: 99%